Hemodialysis in a Child with Pyelonephritis and Nephrolithiasis - Moersintowarti B. Narendra; R.H. Sardjito Djojohadipringgo; Marsetio Donosepoetro (Paediatrica Indonesiana, 1974)
Several events of hemodialysisamong adults have been published inIndonesia; this report might be thefirst done in a child.